Proceedings of the 19th International Conference on Information Integration and Web-Based Applications &Amp; Services 2017
DOI: 10.1145/3151759.3151761
|View full text |Cite
|
Sign up to set email alerts
|

Ex-situ technology appropriation of an e-deliberation platform in an art gallery

Abstract: When designing interactive web applications and services, understanding the situated nature of interaction and investigating technology appropriation experiences in the context of real-world use deserve special attention. In this paper, we report on experiences with technology appropriation of an e-Deliberation platform that we designed to support collaborative interpretation in an art gallery. Our qualitative study is based on interviews with 23 participants to explore a) visitors' practices when commenting o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…When they were outside the gallery, they had read-access only. Secondly, we found that for writing a coherent art interpretation, visitors prefer to be in a relaxed atmosphere (Al Zubaidi et al, 2017). The visitors mentioned they need more time to reflect upon the artwork to write an elaborate text.…”
Section: Short Messages Vs Coherent Textmentioning
confidence: 89%
See 4 more Smart Citations
“…When they were outside the gallery, they had read-access only. Secondly, we found that for writing a coherent art interpretation, visitors prefer to be in a relaxed atmosphere (Al Zubaidi et al, 2017). The visitors mentioned they need more time to reflect upon the artwork to write an elaborate text.…”
Section: Short Messages Vs Coherent Textmentioning
confidence: 89%
“…Based on these results, the participants were invited to write a new interpretation that integrated ideas from highlighted interpretations. The HBGA allows citizens to find common ground and a shared solution, proposal or a collaboratively written text as the result of a collaborative process (Al Zubaidi- Polli et al, 2017). In summary, using the contextual consensus as a design concept means inviting constructive, moderated participation that is supported by a human-based genetic algorithm.…”
Section: Contextual Consensusmentioning
confidence: 99%
See 3 more Smart Citations